Inflammasome activity in leucocytes decreases with abdominal aortic aneurysm progression - Erhart, Philipp; Cakmak, Sinan; Grond-Ginsbach, Caspar; Hakimi, Maani; Böckler, Dittmar; Dihlmann, Susanne (International journal of molecular medicine, 2019)
Abdominal aortic aneurysms (AAAs) are characterized by chronic inflammatory cell infiltration. The present extended immunohistochemistry study aimed to characterize inflammation in AAA and aortic control samples. In specific, the composition of the infiltrating immune cells and the expression of five inflammasome components in these immune cells were evaluated, in order to characterize their role in AAA development. A total of 104 biopsies from 48 AAA patients and 40 healthy specimens from organ donors were evaluated for their grade of inflammation. Infiltrating leukocytes were characterized by specific markers (CD3, CD20 and CD68), intramural localization and inflammasome protein expression [NLR family pyrin domain containing 3 (NLRP3), absent in melanoma 2 (AIM2), apoptosis‑associated speck‑like protein containing a caspase recruitment domain (ASC), Caspase‑1 and Caspase‑5]. Macrophages, B and T lymphocytes were detected to a similar extent in grade 1, 2 and 3 AAA specimens, whereas in control samples, B and T lymphocytes were rarely observed in grade 1 lesions. Expression frequencies of NLRP3, AIM2 and Caspase‑5 were significantly higher in grade 1 lesions of AAA samples compared with grade 1 lesions in control samples. Finally, AIM2, ASC, and Caspase‑5 displayed significantly lower expression frequencies in grade 3 compared with grade 2 AAA specimens, and all inflammasome components were less frequently detected in grade 3 than in grade 1 lesions of AAA. This indicates that inflammasome activities decrease with AAA progression in infiltrating leukocytes. No statistically significant association was found for grade 2 and grade 3 lesions and total leukocyte count, C‑reactive protein levels, maximal aortic diameter, plasma cholesterol level or biomechanical parameters (derived from finite element analysis) of the respective patients. Overall, the aortic wall of AAA contained lymphocytes and macrophages with different states of activity. The present data suggested that therapeutic inhibition of specific inflammasome components might counteract AAA development and progression.